Comparative analysis of selected data recovery software - Tomasz Szymczyk; Rafał Wróbel (Journal of Computer Sciences Institute)
This article presents a comparative analysis of the effectiveness of selected free versions of data recovery software on different storage media such as SSD, HDD, external USB memory stick and SD memory card. The study included the length of scanning and recovery operations and the quality of recovered files. The results of the performance tests were clearly presented in graphs and tables. Conclusions were drawn from the analysis to summarise the experiment.